Beyond Wishful Thinking: The Promise of Science Engagement at the Community Level in Africa. Issue 2 (June 2020) - Amzat, Jimoh
This article discusses the impediments to science-community engagement and identifies five forms of underdevelopment sentiments: primordial, mystical, ethnoreligious, conspiracy, and fatalistic. It also critically examines wishful thinking, which takes the form of superficial recommendations that do not hold any implications for society except on the paper on which they are written. This article argues that both inadequate community-science engagement and wishful thinking are inimical to the African transformation agenda. The article explains community engagement (CE) as a "practical" paradigm and approach to action research, which provides a way of moving beyond wishful thinking. CE is an implementation research approach that can replace wishful thinking with practical solutions by building a community's capacity to address its issues scientifically and sustainably. The article concludes that it is through engagement with science and community-oriented implementation research that desired transformations can be achieved in Africa.